Effect of the plasma size on pedestal and global confinement and prediction for ITER with IMEP - T. Luda; C. Angioni; F. Stefanelli; C. Bourdelle; D. Fajardo; M. Dunne; E. Fable; G. Tardini (Nuclear Fusion, 2025)
Accurately predicting the performance of fusion reactors like ITER is challenging due to uncertainties in scaling laws and limited validation of integrated models. This work presents numerical plasma size scans using the Integrated Model based on Engineering Parameters (IMEP) to investigate its capability to correctly capture the effect of the plasma size on pedestal and global confinement. The scans reveal that IMEP predictions closely align with IPED and the IPB98(y,2) scaling law, and suggest more optimistic confinement trends than the ITPA20-IL scaling law. Simulations of the ITER 15 MA baseline are presented, where IMEP predicts a fusion power of 600 MW and a gain of Q  = 12, with pedestal pressures comparable to EPED predictions. The analysis highlights the impact of fueling methods, separatrix density, heating power, and rotation on confinement and performance, emphasizing the need for robust models to account for pedestal and core dynamics. These findings enhance confidence in IMEP predictions for ITER and future reactors, demonstrating its efficacy in investigating the impact of various factors on fusion performance, pedestal and global confinement.